Renal Thrombotic Microangiopathy in Concurrent COVID-19 Vaccination and Infection - Marco De Fabritiis; Maria Laura Angelini; Benedetta Fabbrizio; Giovanna Cenacchi; Claudio Americo; Stefania Cristino; Maria Francesca Lifrieri; Maria Cappuccilli; Alessandra Spazzoli; Loretta Zambianchi; Giovanni Mosconi (Pathogens, 2021)
We report on the development of nephrotic proteinuria and microhematuria, with histological features of renal thrombotic microangiopathy (TMA), following the first dose of BNT162b2 COVID-19 vaccine (Pfizer-BioNTech) and COVID-19 diagnosis. A 35-year-old previously healthy man was admitted at our hospital due to the onset of foamy urine. Previously, 40 days earlier, he had received the first injection of the vaccine, and 33 days earlier, the RT-PCR for SARS-CoV-2 tested positive. Laboratory tests showed nephrotic proteinuria (7.9 gr/day), microhematuria, serum creatinine 0.91 mg/dL. Kidney biopsy revealed ultrastructural evidence of severe endothelial cell injury suggestive of a starting phase of TMA. After high-dose steroid treatment administration, complete remission of proteinuria was achieved in a few weeks. The association of COVID-19 with renal TMA has been previously described only in patients with acute renal injury. Besides, the correlation with COVID-19 vaccine has not been reported so far. The close temporal proximity (7 days) between the two events opens the question whether the histological findings should be ascribed to COVID-19 itself or to vaccine injection.